Biodegradable Waste Sorbents for Oil Spill Treatment - Imtiyaz Akbar, Najar; Showkat Ahmad, Bhawani; Aamir Hussain, Bhat; Raudhah, Ahmadi; Shanshan, Tang; Yunika Kirana, Abdul Khalik; Nadeem Akbar, Najar (Springer Nature, 2025)
The environmental and economic consequences of oil spills make them a worldwide concern. To address this issue, several commercial systems have been developed to mitigate and control oil spills. Among these systems, the utilization of biodegradable sorbents has emerged as an effective approach. These sorbents have the advantage of being capable of breaking down naturally over time, reducing the long-term impact of oil spills on the environment. Biodegradable sorbents are emerging as a sustainable and environmentally friendly solution for oil spill treat- ment. Derived from natural and renewable sources, these sorbents possess the ability to adsorb or absorb oil, facilitating containment and recovery efforts. This chapter provides an overview of the characteristics, applications, and benefits of biodegradable waste sorbents in oil spill treatment. This chapter highlights various types of biodegradable sorbents, including natural fiber sorbents, cellulose-based materials, agricultural by-products, mushroom spent substrate, and alginate-based materials. These sorbents exhibit high oil sorption capacities and can be deployed in oil spill response, shoreline clean-up, marsh and wetland restoration, and controlled treatment facilities. Biodegradable waste sorbents offer advantages such as reduced dependence.